2021
DOI: 10.1155/2021/5514726
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Distinct Molecular Subtypes of Diffuse Large B Cell Lymphoma Patients Treated with Rituximab‐CHOP Are Associated with Different Clinical Outcomes and Molecular Mechanisms

Abstract: Objective. Our purpose was to characterize distinct molecular subtypes of diffuse large B cell lymphoma (DLBCL) patients treated with rituximab-CHOP (R-CHOP). Methods. Two gene expression datasets of R-CHOP-treated DLBCL patients were downloaded from GSE10846 ( n = 233 , training set) and GSE31312 ( n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Differential expression of CD160 , ISYNA1 and RAD51B has been correlated to the clinical characteristics in various types of cancer. Yu et al ( Yu et al, 2021 ) observed elevated mRNA levels of CD160 in diffuse large B cell lymphoma, especially in subtype I, which displayed poorer overall survival time and progression-free survival time than those in subtype II. Nagashima et al ( Nagashima et al, 2018 ) found significantly higher expression of ISYNA1 in high-grade gliomas than in primary central nervous system lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…Differential expression of CD160 , ISYNA1 and RAD51B has been correlated to the clinical characteristics in various types of cancer. Yu et al ( Yu et al, 2021 ) observed elevated mRNA levels of CD160 in diffuse large B cell lymphoma, especially in subtype I, which displayed poorer overall survival time and progression-free survival time than those in subtype II. Nagashima et al ( Nagashima et al, 2018 ) found significantly higher expression of ISYNA1 in high-grade gliomas than in primary central nervous system lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%